Aggregation induced emission – emissive stannoles in the solid state. Issue 68 (4th August 2020) - Ramirez y Medina, Isabel-Maria; Rohdenburg, Markus; Lork, Enno; Staubitz, Anne
Abstract : For the first time, six classical stannoles with photoluminescence quantum yields of up to 11.1% in the crystalline state and 24.4% in the thin film state are presented. Abstract : The optoelectronic and structural properties of six stannoles are reported. All revealed extremely weak emission in solution at 295 K, but intensive fluorescence in the solid state with quantum yields ( Φ F ) of up to 11.1% in the crystal, and of up to 24.4% ( Φ F ) in the thin film.